One versus Two Venous Anastomoses in Anterolateral Thigh Flap Reconstruction after Oral Cancer Ablation. Issue 2 (August 2016) - Lee, Yao-Chou; Chen, Wei-Chen; Chen, Szu-Han; Hung, Kuo-Shu; Hsiao, Jenn-Ren; Lee, Jing-Wei; Shieh, Shyh-Jou
Abstract : Background: Whether one-vein or two-vein drainage yields better outcomes in anterolateral thigh flap reconstruction after oral cancer ablation is still being debated. Thus, the authors investigated this question. Methods: In this retrospective cohort study, the authors reviewed the charts of 321 patients with oral cancer who, between August of 2010 and July of 2014, had undergone ablative surgery and then immediate reconstruction with the anterolateral thigh flap. Patients who underwent simultaneous reconstruction with additional free flaps were excluded. The patients were subgrouped into newly diagnosed ( n = 221) and previously treated ( n = 100) groups and then subgrouped into one-vein and two-vein groups. Results: Overall, operative time was significantly longer (366.8 ± 112.7 minutes versus 336.3 ± 99.7 minutes; p = 0.009) and hospitalization was significantly shorter (22.0 ± 13.3 days versus 24.5 ± 13.8 days; p = 0.027) in the two-vein group. In the newly diagnosed two-vein group, operative time was also significantly longer (355.5 ± 91.7 minutes versus 319.9 ± 95.9 minutes; p = 0.008), anterolateral thigh flap take-backs for vascular compromise (3.2 percent versus 10.9 percent; p = 0.041) and venous congestion (1.1 percent versus 7.8 percent; p = 0.027) were fewer, and flap survival was greater (100 percent versus 95.3 percent; p = 0.041). Differences between the one-vein and two-vein previously treated subgroups were not significant. Conclusion: In newly diagnosed patients undergoing anterolateral thigh flap reconstruction after oral cancer ablation, better outcomes are achieved with two venous anastomoses rather than one. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.